Legal Protection of Consumers with Online Transactions - Suwardi; Rossa Ilma Silfiah; Humiati; Kristina Sulatri; Yudhia Ismail (Dinasti Research, 2024)
With the existence of a new legal regime known as cyber law or telematics law, the transaction system makes it easier for users. Cyber law or cyber law is used by utilizing information and communication technology which is a manifestation of the convergence of telecommunications law, media law and information law. The legal problems that are often faced are related to information, communication and/or transactions, especially in terms of evidence related to legal actions carried out by electronic systems. This writing aims to provide legal protection for consumers with online transactions. The research method used is normative juridical research, which involves analysis of theories, concepts, legal principles and statutory regulations relevant to this research topic. The legal problems that are often faced are related to the delivery of information, communi cation and/or transactions electronically, especially in terms of evidence and matters related to legal actions carried out through electronic systems. The results of this research can be concluded: First, in the form of legal protection for consumers who make online transactions as regulated in Law Number 11 of 2008 concerning Information and Electronic Transactions as well as provisions for legal protection for consumer users with online transactions or e-commerce. Second, in the form of responsibility for parties involved in online transactions or e-commerce as stated in Law Number Article 12 paragraph 3 concerning Information and Electronic Transactions, it is explained that every person who violates the obligation to carry out electronic transactions must be responsible for all losses and the resulting legal consequences.